To find the correct table that reflects the equation \( y = -f(x) \), we need to understand that this transformation results in the y-values being the negative of the original y-values. If \( f(x) \) is the original function, then \( -f(x) \) will be the reflection of that function over the x-axis.
Let's analyze the given options:
-
Option 1:
- \( x \) | \( -f(x) \)
- 2 | 0
- 3 | 1
- 6 | 2
It implies that \( f(2) = 0 \), \( f(3) = -1 \), and \( f(6) = -2 \) which is inconsistent because \( -f(3) = 1 \) should imply \( f(3) = -1 \), and similarly for others.
-
Option 2:
- \( x \) | \( -f(x) \)
- -2 | 0
- -3 | -1
- -6 | -2
It implies that \( f(-2) = 0 \), \( f(-3) = 1 \), and \( f(-6) = 2\), which is again inconsistent because \( -f(-3) = -1 \) must imply \( f(-3) = 1 \).
-
Option 3:
- \( x \) | \( -f(x) \)
- 2 | 0
- 3 | -1
- 6 | -2
Here, it implies \( f(2) = 0 \), \( f(3) = 1 \), and \( f(6) = 2 \). This is consistent because \( -f(3) = -1 \) matches.
-
Option 4:
- \( x \) | \( -f(x) \)
- -2 | 0
- -3 | 1
- -6 | 2
This implies that \( f(-2) = 0 \), \( f(-3) = -1 \), and \( f(-6) = -2 \), which is inconsistent for the same reasons as above.
The only table that shows \( y = -f(x) \) correctly reflecting over the x-axis is Option 3:
- \( x = 2 \) has \( -f(2) = 0 \)
- \( x = 3 \) has \( -f(3) = -1 \), meaning \( f(3) = 1 \)
- \( x = 6 \) has \( -f(6) = -2 \), meaning \( f(6) = 2 \)
Thus, the answer is Option 3.